2020
DOI: 10.1111/bju.15132
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative frailty and outcome in patients undergoing radical cystectomy

Abstract: Objective To determine the value of preoperative frailty screening in predicting postoperative severe complications and 1‐year mortality in patients undergoing radical cystectomy (RC). Patients and Methods Prospective cohort single‐centre study in patients undergoing RC from September 2016 to December 2017. Preoperative frailty screening was implemented as standard care and was used to guide shared decision‐making during multidisciplinary team meetings. Frailty screening consisted of validated tools to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…For this kind of elderly and obese patients, the decreased skeletal muscle content and frailty significantly diminished their capacity to tolerate RC and urinary diversion surgery and impacted perioperative outcomes and long‐term postoperative prognosis. Related studies had shown that frail patients have an increased rate of perioperative complications and an increased risk of death after surgery 31,32 . While effective weight management and lifestyle intervention can reduce the complications caused by obesity, improving the frailty of patients and their QoL 33 .…”
Section: Discussionmentioning
confidence: 99%
“…For this kind of elderly and obese patients, the decreased skeletal muscle content and frailty significantly diminished their capacity to tolerate RC and urinary diversion surgery and impacted perioperative outcomes and long‐term postoperative prognosis. Related studies had shown that frail patients have an increased rate of perioperative complications and an increased risk of death after surgery 31,32 . While effective weight management and lifestyle intervention can reduce the complications caused by obesity, improving the frailty of patients and their QoL 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that frailty was associated with the treatment modality selection, type of urinary diversion, and adverse postoperative outcomes. [22][23][24] In addition, frailty was associated with an increased odds of delayed GI function recovery or the rate of POI or anastomotic leakage in patients who underwent elective colorectal cancer resections. These findings suggest that there is an association between frailty and the delayed bowel function or POI.…”
Section: Discussionmentioning
confidence: 99%
“…Complications are mostly caused by surgical stress, particularly age and physical conditions, all of which have recently been found as predictors of higher complication rates. 17 , 24 , 25 We used the ACCI in our study to account for patients' characteristics. However, our findings revealed that age and ACCI scores were not prognostic indicators for severe complication rates, neither the CDC nor the CCI grading exhibited statistically significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Complications are mostly caused by surgical stress, particularly age and physical conditions, all of which have recently been found as predictors of higher complication rates 17,24,25 . We used the ACCI in our study to account for patients' characteristics.…”
Section: Discussionmentioning
confidence: 99%